Patient of carcinoma cervix presenting with oculomotor palsy due to meningeal carcinomatosis- a case report - Kaur, Harharpreet; Girgila, Kawalinder; Kaur, Inderjit (International Journal of Research in Medical Sciences, 2016)
We report a case of isolated pupil involving oculomotor nerve palsy as the inaugural and the only clinical sign of meningeal carcinomatosis (MC) in a patient of carcinoma of cervix. There were no other neurological signs and symptoms except for headache. The first MRI was unremarkable but a repeat MRI after 15 days showed meningeal enhancement which pointed towards the diagnosis. The CSF was also normal. This case highlights the importance of considering MC in all patients who develop sudden ptosis due to oculomotor palsy in a cancer patient even if MRI is normal.